2018
DOI: 10.1002/ece3.4446
|View full text |Cite
|
Sign up to set email alerts
|

Prey exploitation and dispersal strategies vary among natural populations of a predatory mite

Abstract: When predators commonly overexploit local prey populations, dispersal drives the dynamics in local patches, which together form a metapopulation. Two extremes in a continuum of dispersal strategies are distinguished: the “Killer” strategy, where predators only start dispersing when all prey are eliminated, and the “Milker” strategy, in which predator dispersal occurs irrespective of prey availability. Theory shows that the Milker strategy is not evolutionarily stable if local populations are well connected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…The spider mite culture was kept on Lima bean plants (Phaseolus lunatus) in a climate room (26 °C, 60% RH and 16L:8D) and was used to maintain the predator cultures described below. We used two lines of P. persimilis that were selected for early and late dispersal (Revynthi 2017). Six rounds of selection were performed to create these lines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spider mite culture was kept on Lima bean plants (Phaseolus lunatus) in a climate room (26 °C, 60% RH and 16L:8D) and was used to maintain the predator cultures described below. We used two lines of P. persimilis that were selected for early and late dispersal (Revynthi 2017). Six rounds of selection were performed to create these lines.…”
Section: Methodsmentioning
confidence: 99%
“…Here we aim to investigate whether late dispersers indeed cannibalise more than early dispersers, making use of selection lines of P. persimilis that show different dispersal and exploitation strategies (Revynthi 2017), i.e., predators that depart early and late from a patch with spider mite prey. Even though we have information about the dispersal and exploitation strategies of these two selected lines, little is known about their cannibalistic tendencies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that some individuals do not perform behavioural strategies. This happens because they have not yet learned or, somehow, they cannot put the tactic into practice 34 , 39 , 40 . Therefore, to make the model more realistic, we describe the individual’s ability to execute the tactic by defining a conditioning factor.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, within population lineages exceeded a critical inbreeding coefficient in the F 2 generation (Fig 2), beyond which inbreeding depression effects became similar to those of lineages founded by sib-mated females. At the individual phenotypic level, genetic deficiencies associated with increasing inbreeding levels, may have adversely affected diverse inter-related physiological, life history and/or behavioral traits, such as decreasing general stress resilience, decreasing tolerance of energetic constraints, increasing mortality, prolonging development, decreasing fecundity, decreasing competitive abilities, and promoting the occurrence of cannibalism and dispersal tendencies [27,55,56,57]. Pinpointing the phenotypic mechanisms underlying the differences in performance of isolated lineages emerging from in- and out-bred founders requires additional experimental work.…”
Section: Discussionmentioning
confidence: 99%